In Situ Peptide Assembly for Cancer Therapy - Guowei Liang; Xianbao Sun; Yu Ma; Tiantian Xia; Xiaotong Cheng; Gaolin Liang (Angewandte Chemie International Edition, 2026)
ABSTRACT Peptides have emerged as promising anticancer agents due to their biocompatibility and functional versatility, such as tumor targeting and cell penetrating capabilities. However, their clinical application is often limited by poor stability and rapid clearance. To overcome these drawbacks, peptide assembly strategies have been developed. Early approaches utilized preassembled peptide nanomaterials, but these approaches faced challenges in circulation and tumor penetration. Recently, in situ peptide assembly has gained increasing attention. This strategy involves administering molecular peptide‐drug precursors that undergo stimulus‐responsive activation in the tumor microenvironment to form nanostructures locally. This process utilizes an aggregation‐induced retention (AIR) effect for enhanced drug enrichment and retention at the tumor site. Furthermore, these in situ‐formed nanoassemblies can disrupt intracellular homeostasis and induce apoptosis, amplifying therapeutic outcomes. This review systematically elaborates on the mechanisms of in situ peptide assembly, classifies the diverse stimuli triggering this process, and comprehensively summarizes its applications in cancer therapy. Finally, current challenges and prospects in this advancing field are discussed.